Manual de identidad corporativa, para la comunicación institucional de la Universidad Nacional de Loja - Gutiérrez Quizhpe, Byron Vicente (2016)
The thesis called "CORPORATE IDENTITY MANUAL FOR INSTITUTIONAL COMMUNICATION OF NATIONAL UNIVERSITY OF LOJA". The main problem of the research was: How to apply a corporate identity manual aimed at the National University of Loja?, as this belongs to the visual identity of the institution formed by the logo and its applications, as well as the book store structure available in the institution as a working and control tool. Our overall aim refers to realize a Corporate Identity Manual for the Institutional Communication of the National University of Loja. The methods used were scientific, deductive, analytical and statistical. While the techniques were the survey and interview. Also several instruments as a camera, audio recorder and data logging were used. The results showed that the university community consider that should be an implement of a Corporate Identity Manual, this refers to question 3, Would you like the UNL had a Corporate Identity Manual?, 229 people that are 79% say that there should be an implement of a corporate identity manual. As for the interviews referred to Question 2, Do you think it would be good to implement a Corporate Identity Manual?, so that interviwed people generally agree that it would be very important to create a manual. They agree it is neccesary the existance of a corporate image which attracts attention, where it is easy to understand and express credibility and trust, thus positioning the institution. Generate in the university community a clear idea of how impacts a manual of corporate identity in an institution and in fact how to standardize the use of its elements.